Internal Hernia After Laparoscopic Left Colectomy: Case Series and Review of the Literature - Tueme-de la Peña, Danilo; Acosta-Flores, José Adolfo; Garza-Cantú, Alan Alejandro; Rangel-Ríos, Hugo Antonio; Chapa-Lobo, Alberto Félix; Salgado-Cruz, Luis Enrique (Journal of Coloproctology, 2022)
Objective Laparoscopic colectomy has gained acceptance as a standard treatment for benign and malignant colorectal disease, such as diverticular disease and cancer, among others. Same as in open surgery, the laparoscopic approach carries a low risk of small bowel obstruction in the postoperative period, but in laparoscopic surgery, internal hernia after laparoscopic left colectomy may be a cause of small bowel obstruction with a significant risk of morbidity and mortality. This rare complication may be prevented with routine closure of the mesenteric defects created during the colectomy.Methods We present four cases of internal herniation after laparoscopic colectomy. Two cases were after laparoscopic left colectomy and two after laparoscopic low anterior resection. All four cases had full splenic flexure mobilization. Routine closure of the mesenteric defect was not performed in the initial surgery.Results The four patients were treated by laparoscopic reintervention with closure of the mesenteric defect. In two of them, conversion to open surgery was necessary. One of the patients developed recurrent internal herniation after surgical reintervention with mesenteric closure of the defect. All patients were managed without need for bowel resection, and mortality rate was 0%.Conclusion Internal herniation after laparoscopic colorectal surgery is a highly morbid complication that requires prompt diagnosis and management and should be suspected in the early postoperative period. Additional studies with extended follow-up are required to establish recommendations regarding its prevention and management.
Keywords: laparoscopic left hemicolectomy; internal hernia; lesser omental sac; mesenteric defect; laparoscopic low anterior resection